2013
DOI: 10.1136/thoraxjnl-2013-204457.347
|View full text |Cite
|
Sign up to set email alerts
|

P195 Plume characteristics of fluticasone propionate/formoterol pMDI compared with fluticasone propionate/salmeterol pMDI: Abstract P195 Table 1.

Abstract: Background Methotrexate (MTX) immunosuppressive therapy is selectively used to assist with the reduction of the oral corticosteroid demand thereby decreasing the risk of potential side effects in individuals with steroid dependant asthma. Previous reported data has demonstrated similar significant reduction in corticosteroid load, asthma exacerbation and hospital admission rate. This study aims to compare similar variables collated from UK severe asthma specialist centres to further generate evidence for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A rapid onset of action may be an important attribute of an ICS/LABA maintenance therapy for patients [4,8]; recent studies have suggested that therapies with a rapid onset of bronchodilation may encourage patient adherence to their treatment regimen [9,10]. Furthermore, fluticasone/formoterol has been shown in vitro to have a high fine particle fraction (FPF), to exhibit negligible flow-rate dependency [11], and has also demonstrated a slow, warm and prolonged aerosol plume [ [12]; unpublished data] factors which may correlate with corresponding high levels of lung deposition in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…A rapid onset of action may be an important attribute of an ICS/LABA maintenance therapy for patients [4,8]; recent studies have suggested that therapies with a rapid onset of bronchodilation may encourage patient adherence to their treatment regimen [9,10]. Furthermore, fluticasone/formoterol has been shown in vitro to have a high fine particle fraction (FPF), to exhibit negligible flow-rate dependency [11], and has also demonstrated a slow, warm and prolonged aerosol plume [ [12]; unpublished data] factors which may correlate with corresponding high levels of lung deposition in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the percentage of respirable fraction contained in the aerosol (defined as drug particles with the diameter range between 2 and 5 μm) correlates with the drug deposition in lung tissues [57,58]. The inhaler used for the administration of the fluticasone propionate/ formoterol combination ensures the distribution of an aerosol with a respirable fraction of 40% of the inhaled dose [59], which is consistent at different inspiratory flows, with a plume value of 168 ms [60]. These characteristics facilitate drug deposition throughout the airways.…”
Section: Alternative Reliever Treatments Include Inhaled Anticholinermentioning
confidence: 99%